Towards the fully automated monitoring of ecological communities - Marc Besson; Jamie Alison; Kim Bjerge; Thomas E. Gorochowski; Toke T. Høye; Tommaso Jucker; Hjalte M. R. Mann; Christopher F. Clements (Ecology Letters, 2022)
High‐resolution monitoring is fundamental to understand ecosystems dynamics in an era of global change and biodiversity declines. While real‐time and automated monitoring of abiotic components has been possible for some time, monitoring biotic components—for example, individual behaviours and traits, and species abundance and distribution—is far more challenging. Recent technological advancements offer potential solutions to achieve this through: (i) increasingly affordable high‐throughput recording hardware, which can collect rich multidimensional data, and (ii) increasingly accessible artificial intelligence approaches, which can extract ecological knowledge from large datasets. However, automating the monitoring of facets of ecological communities via such technologies has primarily been achieved at low spatiotemporal resolutions within limited steps of the monitoring workflow. Here, we review existing technologies for data recording and processing that enable automated monitoring of ecological communities. We then present novel frameworks that combine such technologies, forming fully automated pipelines to detect, track, classify and count multiple species, and record behavioural and morphological traits, at resolutions which have previously been impossible to achieve. Based on these rapidly developing technologies, we illustrate a solution to one of the greatest challenges in ecology: the ability to rapidly generate high‐resolution, multidimensional and standardised data across complex ecologies.

Predation drives recurrent convergence of an interspecies mutualism - William E. Feeney; Rohan M. Brooker; Lane N. Johnston; James D. J. Gilbert; Marc Besson; David Lecchini; Danielle L. Dixson; Peter F. Cowman; Andrea Manica (Ecology Letters, 2019)
Mutualisms are important ecological interactions that underpin much of the world's biodiversity. Predation risk has been shown to regulate mutualism dynamics in species‐specific case studies; however, we lack studies which investigate whether predation can also explain broader patterns of mutualism evolution. We report that fish‐anemone mutualisms have evolved on at least 55 occasions across 16 fish families over the past 60 million years and that adult body size is associated with the ontogenetic stage of anemone mutualisms: larger‐bodied species partner with anemones as juveniles, while smaller‐bodied species partner with anemones throughout their lives. Field and laboratory studies show that predators target smaller prey, that smaller fishes associate more with anemones, and that these relationships confer protection to small fishes. Our results indicate that predation is likely driving the recurrent convergent evolution of fish‐anemone mutualisms and suggest that similar ecological processes may have selected convergence in interspecies interactions in other animal clades.